Data, New Technologies, and Global Imbalances Beyond the Obvious - Kotrotsios, Georges (Cambrdige Scholars Publishing, 2021)
We are familiar with the idea that technology is neutral, and that its impact depends only on how it is used. This traditional view has, however, become untenable. Because of its nature and its complex interplay with industry, the economy, and society, technology is no longer neutral. This change is being driven by the pervasiveness of data, which today are generated everywhere at an unpreceded pace because several technologies are currently reaching maturity. Data shape the world around us, in a trend that is commonly referred to as ""digitalization"". This trend is apparent in every aspect o.